Oil Prices and Economic Stability: The Macroeconomic Impact of Oil Price Shocks on the Swedish Economy - Bengt-Christer Ysander (The Research Institute of Industrial Economics (IUI), 1981)
In these simulation experiments for the Swedish economy, the impact of a future oil price shock was measured in terms of the stabilization policies required, and the possibility was evaluated of insuring against such price shocks by way of a gradually increasing oil tax.
Keywords: C90; E32; H21; L60; 330; Pricing experiment; Oil; Price shock